Behavioral Response of Rhyzopertha dominica, Lesser Grain Borer, to Wheat Volatiles - Conner, Paige; Scheff, Deanna S. (My University, 2018)
The lesser grain borer is a grain pest that eats and damages grain products such as rice, corn, wheat, and millet (Edde, 2012). The lesser grain borer has a tendency to to reproduce rapidly and explode into big infestations under optimal conditions, which become hard to control (Johnson, 2000). Controlling these infestations has been moderately successful with the use of pheromones, which attract the beetles (El-Azi, 2011). The purpose of this research is to pinpoint the lesser grain borer’s potential preference of different wheat volatiles it is given, and find the strongest response. The hypothesis is that certain samples that have higher moisture, a stronger odor, or an added pheromone that could elicit the strongest response to the volatiles than samples that do not have these conditions. The results obtained from this research indicate that our hypothesis is fairly correct, showing the aged, wet wheat with an added pheromone had the highest preference among all samples tested. The significance of this research should bring the gap closer between effectively controlling the lesser grain borer and grain safety, which will maximize the product, reduce the potential hazards to human health, and be the framework for other similar problems with grain pests around the world
Keywords: Fall 2018